The Influence of Knowledge Management, Physical Non-Physical Environment and Skills on the Performance of Semarang City Diskominfo Employees - Ardhianto Ardhianto; Noviana Devi; Weny Saputri; Artha Febriana (Jurnal Telekomunikasi dan Informatika, 2024)
This research aims to analyze and find out how knowledge management, work environment and skills influence employee performance at Diskominfo Semarang City. The objects of this research are all employees Diskominfo Semarang City. as many as 158 employees. In determining the sample size, researchers used the census method where all members of the population were used as the research sample. The number of samples in this research was 158 employees. Trials of research items were carried out on 15 employees. Validity test uses Pearson Product Moment correlation. Meanwhile, the reliability test uses Cronbach Alpha. Data collection techniques include questionnaires, observation and documentation. Analysis prerequisite tests include, multicollinearity tests and heteroscedasticity tests. The data analysis technique used is multiple linear regression. The research results show that: (1) Knowledge management has no significant effect on employee performance. (2) Work environment has no significant effect on employee performance. (3) Skill have a positive and significant effect on employee performance